Trajectory of Fifths in Tonal Mode Detection - Tomasz Lukaszewicz; Dariusz Kania (IEEE Access)
The article introduces a novel algorithm designed to distinguish between the major and minor tonal modes in musical compositions. It utilizes parameters derived from the trajectory of fifths obtained for a given piece: the angular coordinates of the trajectory’s first and last points, the orientation of the trajectory’s characteristic vector, and a coefficient quantifying the imbalance in the distribution of trajectory points between quadrants associated with major and minor modes. To assess the algorithm’s effectiveness, experiments were conducted using selected sets of Bach and Chopin works transposed into C major and A minor keys, as well as on pieces from the Saarland Music Data: MIDI-Audio Piano Music in their original keys. The results indicate high detection accuracy, demonstrating the algorithm’s potential for reliable tonal mode identification.